Burden of Neck Pain and Associated Factors Among Sewing Machine Operators of Garment Factories in Mekelle City, Northern Part of Ethiopia, 2018, A Cross-Sectional Study - Gebremedhin H. Biadgo; Gebrerufael S. Tsegay; Sumeya A. Mohammednur; Berihu F. Gebremeskel (Elsevier, 2021)
Background: Neck pain is a major public health problem among sewing machine operators working in textile factories. Even though the textile industries are growing in number in Ethiopia, but there is a dearth of published studies on the prevalence of neck pain. Therefore, this study was aimed to assess the prevalence and associated factors of neck pain among sewing machine operators of garment factories in Mekelle city. Method: An institutional-based cross-sectional study design was implemented among 297 sewing machine operators' working in garment factories in Mekelle city. A systematic random sampling technique was used. Data were collected through interviews and analyzed using Statistical Package for Social Science version 23. Finally, variables with 95% confidence interval (CI): p < 0.05 in the multivariate analysis were significantly declared. Results: Two hundred ninety-seven sewing machine operators were enrolled, with 98.7% response rates. In this study, the 12-month prevalence rate of neck pain was found to be 42.3% (95% CI: 36.6%-47.9%), and variables like such as break time [adjusted odds ratio (AOR): 5.888, 95% CI: (2.775-12.493)], working hours per day [AOR: 6.495, 95% CI: (2.216-19.038)], static posture [AOR: 4.487, 95% CI (1.640-12.275)], and repetitive activity [AOR: 4.519, 95% CI:(2.057-9.924)] were associated with neck pain. Conclusion: In this study, neck pain is a major public health problem. Continuous work without break time, working greater than 8 hours per day, sitting in the same position for greater than 2 hours, and high repetitive activities were found significantly associated with neck pain. Owners and governmental bodies need to focus on developing preventive strategies and safety guidelines.